2022
DOI: 10.3390/su141811761
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Spatiotemporal Characteristics and Causes of Rear-End Collisions on Urban Roadways

Abstract: Rear-end collisions are caused by drivers misjudging urgent risks while following vehicles ahead in most cases. However, compared with other accident types, rear-end collisions have higher preventability. This study aims to reveal the prone segments and hours of rear-end collisions. First, we extracted 1236 cases from traffic accident records in Harbin from 2015 to 2019. These accidents are classified as property damage accidents, injury accidents and fatal accidents according to the collision severity. Second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Traffic accident hotspots refer to locations with high-density clusters of traffic accidents. In recent years, based on substantial volumes of traffic accident data and with the help of GIS platforms, in-depth studies on urban traffic accident hotspots have been conducted [9][10][11][12][13]. GIS-based traffic accident hotspot identification methods include the kernel density estimation method, the local Moran's I, the Getis-Ord Gi* method, and so on [14][15][16].…”
Section: Literature Review 21 Traffic Accident Hotspotsmentioning
confidence: 99%
“…Traffic accident hotspots refer to locations with high-density clusters of traffic accidents. In recent years, based on substantial volumes of traffic accident data and with the help of GIS platforms, in-depth studies on urban traffic accident hotspots have been conducted [9][10][11][12][13]. GIS-based traffic accident hotspot identification methods include the kernel density estimation method, the local Moran's I, the Getis-Ord Gi* method, and so on [14][15][16].…”
Section: Literature Review 21 Traffic Accident Hotspotsmentioning
confidence: 99%
“…Extensive transportation research has already found that traffic accidents and crashes occur more frequently in certain places and times and has also explored the behavioral routines and environmental causes and correlates of traffic crashes. Some of these studies focus on larger place and time units, such as higher-density city centers (Alkhadour et al, 2021;Dezman et al, 2016;Rahman et al, 2020;Zhang et al, 2022) or during congested traffic hours (Li et al, 2020;Plug et al, 2011;Zhang et al, 2022). However, a large body of transportation research examines specific behavioral and environmental factors contributing to crashes.…”
Section: Introductionmentioning
confidence: 99%